2020
DOI: 10.1016/j.ebiom.2020.102933
|View full text |Cite
|
Sign up to set email alerts
|

A radiomics model for preoperative prediction of brain invasion in meningioma non-invasively based on MRI: A multicentre study

Abstract: Background Prediction of brain invasion pre-operatively rather than postoperatively would contribute to the selection of surgical techniques, predicting meningioma grading and prognosis. Here, we aimed to predict the risk of brain invasion in meningioma pre-operatively using a nomogram by incorporating radiomic and clinical features. Methods In this case-control study, 1728 patients from Beijing Tiantan Hospital (training cohort: n = 1070) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 42 publications
6
49
0
Order By: Relevance
“…[60][61][62][63][64] A few studies have addressed the prognosis of meningiomas. 65,66 Morin et al enrolled 314 patients with meningiomas and reasonably included many cases of higher grades of meningiomas (57% grade I, 35% grade II, and 8% grade III). 67 They demonstrated an accuracy of up to 77% for overall survival using a random forest classifier incorporating both MRTA and non-MRTA features.…”
Section: Texture Analysis In Other Brain Tumorsmentioning
confidence: 99%
“…[60][61][62][63][64] A few studies have addressed the prognosis of meningiomas. 65,66 Morin et al enrolled 314 patients with meningiomas and reasonably included many cases of higher grades of meningiomas (57% grade I, 35% grade II, and 8% grade III). 67 They demonstrated an accuracy of up to 77% for overall survival using a random forest classifier incorporating both MRTA and non-MRTA features.…”
Section: Texture Analysis In Other Brain Tumorsmentioning
confidence: 99%
“…This novel method has the potential to increase molecular knowledge of the tumor in a noninvasive manner, which is beneficial given the tumor's hard-to-access location. Several studies showed a potential role of radiomics in predicting the pathological grade, subtypes, recurrence and brain invasion of meningiomas, [32][33][34][35][36] and could also be helpful for differential diagnosis [37][38][39][40]. For example, a study on 175 meningioma patients, of which 103 were low grade and 72 high grade, showed a strong association between 12 MRI radiographic features and histopathological grade [32].…”
Section: Reviewmentioning
confidence: 99%
“…The results of this study evidenced that four radiomics features (roundness of FLAIR-shape, cluster shades of FLAIR/T1CE gray level, DWI/ADC gray level variability and FLAIR/T1CE gray level energy) have a strong predictive value for higher tumor grades. Furthermore, a multicenter study on 1728 patients with grade I, II and III meningiomas showed that 16 clinicoradiomic features present a high sensitivity for risk prediction of brain invasion in meningioma [ 40 ]. The development of radiomics in meningiomas can be of great relevance in clinical practice, considering the potential role of imaging-derived features in deepening the knowledge on tumor biology and pathology and the potential prognostic or predictive implication.…”
Section: Radiological Featuresmentioning
confidence: 99%
“…More recently, a multicenter study has shown that radiomic features have the potential of preoperatively predicting brain invasion in meningioma (45). They have built a SVM model derived from the T1C and T2 MRI sequences and yielded an AUC of 0.819.…”
Section: Other Applications In Meningiomasmentioning
confidence: 99%